2007
DOI: 10.1523/jneurosci.2734-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Attention and the Latency of Neuronal Responses in Macaque Area V4

Abstract: The effects of attention on neuronal responses in visual cortex have been likened to a change in stimulus contrast. Attention and stimulus contrast both modulate the magnitude of neuronal responses. However, changes in stimulus contrast also affect the latency of visual responses. Although many neurophysiological studies have examined how attention affects the strength of neuronal responses, few have considered whether attention affects neuronal latencies. To compare directly the effects of stimulus contrast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
101
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(116 citation statements)
references
References 31 publications
11
101
0
1
Order By: Relevance
“…In the following days, subjects underwent five 1.5-hour fMRI task sessions, consisting of 12 runs of 24 trials for a total of 5 × 12 × 24 = 1440 trials. We chose to scan a small number of highly trained subjects across multiple days in order to maximize our ability to detect parametric changes in the BOLD signal within all conditions, as in other visual studies (Amano et al, 2009;Lee et al, 2007;Silver et al, 2008) and our own previous studies (Kayser et al, 2010a,b).…”
Section: Subject Training and Task Performancementioning
confidence: 99%
“…In the following days, subjects underwent five 1.5-hour fMRI task sessions, consisting of 12 runs of 24 trials for a total of 5 × 12 × 24 = 1440 trials. We chose to scan a small number of highly trained subjects across multiple days in order to maximize our ability to detect parametric changes in the BOLD signal within all conditions, as in other visual studies (Amano et al, 2009;Lee et al, 2007;Silver et al, 2008) and our own previous studies (Kayser et al, 2010a,b).…”
Section: Subject Training and Task Performancementioning
confidence: 99%
“…With regard to transmission times (ii), little evidence supports the notion that attention decreases latency of neural signals, at least in animal models. In single unit neurophysiological studies in monkeys, Lee et al [51] found that directing attention towards (or away from) a stimulus has little effect on the latency of neuronal signals in area V4 (approx. 1 ms decrease in latency for either 100% or 25% contrast stimuli).…”
Section: Human Psychophysical Studiesmentioning
confidence: 99%
“…In addition, the authors were not able to identify or reliably measure C1, the earliest component originating primarily from V1, which could have provided a more direct read-out of early stages of visual processing. One should also bear in mind that even a change in the latency of an ERP component does not necessarily indicate a change in the latency of individual neurons [51]. Each component of the ERP reflects the pooled activity of large ensembles of cells that could have different individual latencies.…”
Section: Neurophysiological Mechanisms Of Relative Timing (A) Human Ementioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2007), in The Journal of Neuroscience, report an important constraint on the similarity between attention and contrast. Most studies that have examined the effects of visual attention have focused on the magnitude of neuronal responses.…”
mentioning
confidence: 99%